2000
DOI: 10.1007/s002650000242
|View full text |Cite
|
Sign up to set email alerts
|

Life history costs of olfactory status signalling in mice

Abstract: Large body size confers a competitive advantage in animal contests but does not always determine the outcome. Here we explore the trade-off between short-term achievement of high social status and longer-term life history costs in animals which vary in competitive ability. Using laboratory mice, Mus musculus, as a model system, we show that small competitors can initially maintain dominance over larger males by increasing investment in olfactory status signalling (scent-marking), but only at the cost of reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 31 publications
1
84
0
1
Order By: Relevance
“…Several researchers have proposed that such expression is a result of sexual selection. This "honest-signal" model predicts that females favor males who can afford high expression despite potential costs (e.g., protein loss or attracting predators and competitors) (18)(19)(20)(21)(22). Although this hypothesis has not been explicitly tested, the observation that MUP concentration declines as mice adapt to captivity (17,23) suggests a possible role of relaxed social and sexual selection.…”
mentioning
confidence: 97%
“…Several researchers have proposed that such expression is a result of sexual selection. This "honest-signal" model predicts that females favor males who can afford high expression despite potential costs (e.g., protein loss or attracting predators and competitors) (18)(19)(20)(21)(22). Although this hypothesis has not been explicitly tested, the observation that MUP concentration declines as mice adapt to captivity (17,23) suggests a possible role of relaxed social and sexual selection.…”
mentioning
confidence: 97%
“…This indicates that males from enlarged litters in the current study might be reaching sexual maturity at a younger age and contributing more resources toward reproductive investment than those from reduced litters. Gosling et al (2000) suggested that smaller male lab mice can maintain dominance over larger males by investing more in olfactory signalling and increased preputial gland mass. This investment appeared to come at a cost, however, because these originally small males had a slower growth rate.…”
Section: Liver Kidneysmentioning
confidence: 99%
“…In male mammals, reproductive behaviors that increase activity levels, such as mate guarding and scramble competition, often have substantial energetic costs, often more than doubling resting energy demands and sometimes exceeding the costs of lactation for females (32). It seems more likely that the elevated behavioral investment in scent-marking and patrolling of their home area for territorial males in this experiment may have been energetically costly, facilitating the reduction in body mass observed in this experiment and previously reported (30). We observed no differences between genotypes for this behavior, although we cannot exclude the possibility that SOD1 deficiency may influence scent-marking in a more subtle manner which was undetectable in our assay.…”
Section: Discussionmentioning
confidence: 46%
“…It has been suggested that the production of MUPs may be energetically costly (30), but the synthesis of these proteins actually makes up a small amount of a mouse's total energy budget. Estimates of the energy costs of protein synthesis range between 3 and 20 kj/g protein (31).…”
Section: Discussionmentioning
confidence: 99%